PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP REPUTASI PERUSAHAAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN (STUDI PADA PT. COCA COLA AMATIL DENPASAR) - Yus Dantara, I Kadek; Rahanatha, Gede Bayu (E-Jurnal Manajemen, 2015)
This study aims to find the effect of corporate social responsibility toward company's repution mediated by customer satisfaction, this study was conducted at PT. Coca Cola Amatil Denpasar by using qualitative research. The datas were gained by spreading questioner to 120 consumers of PT.Coca Cola Amatil product in Denpasar city. Structural equation modeling (SEM) was used to analyze the datas. The results show CSR has positive and significant effect toward company reputation. Customer satisfaction has positive and significant effect toward company reputation. And customer satisfaction was eligible to act as mediation variable in the effect of CSR toward company reputation .
Keywords: Corporate Social Responsibility, Corporate Reputation, Customer Satisfaction